Molecular Epidemiological and Serological Studies of Bovine Leukemia Virus in Taiwan Dairy Cattle - Hsieh, Jui-Chun; Li, Chang-Yan; Hsu, Wei-Li; Chuang, Shih-Te (Frontiers in Veterinary Science, 2019)
Bovine leukemia virus (BLV) infection results in a decrease in milk yield and quality, a compromise in immunity, and shortening in the longevity of cows. The current status of BLV infection of dairy cattle in Taiwan remains unclear. To evaluate BLV infection, anti-BLV gp51 antibody and proviral DNA were detected. Surprisingly, the seroprevalence of BLV at the animal and herd level was as high as 81.8% (540/660 cattle) and 99.1% (109/110 herds), respectively. Among 152 blood samples analyzed, 132 (86.8%) were detected as positive for BLV-proviral DNA. When the complete blood count (CBC) was taken into account, the white blood cell (WBC) number appears to be the factor with the highest predicted potential for BLV infection. Moreover, based on receiver operating characteristic (ROC) curve analysis, the sensitivity and specificity are 72.0% and 75.0%, respectively, when the cut-off value of the WBC was set at 10.215 K/μL. Despite the co-circulation of genotype 1 and 3 in Taiwan, genotype 1 was much more prevalent (29/30). Taken together, due to the high prevalence of BLV, the identification of risk factors for interrupting the routes of transmission of BLV are critical for the control and prevention of further BLV infection.